Authenticity of roasted coffee using1H NMR spectroscopy - de Moura Ribeiro, Marcos Vinícius [UNESP]; Boralle, Nivaldo [UNESP]; Redigolo Pezza, Helena [UNESP]; Pezza, Leonardo [UNESP]; Toci, Aline Theodoro (Elsevier, 2017)
Coffee is globally one of the most widely used food products and is vital to the economies of countries involved in its production and export. Due to its commercial importance, the detection of impurities and foreign matters has been a constant concern in fraud verification, especially because it is difficult to perceive adulterations with the naked eye in samples of roasted and ground coffee. Until now, there has been no comprehensive methodology for identification of the many types of coffee adulterants. This work describes, for the first time, a fast and effective technique using 1H NMR to check for adulteration in roasted coffee. The samples used were a set of commercial Brazilian arabica blends produced from good cup quality beans, and four adulterants (corn, coffee husks, barley, and soybean). The methodology was effective for all the adulterants analyzed in 31 commercial samples.
Keywords: 1H NMR; Adulteration; Authenticity; Coffee quality; Control quality; Food analysis; Food composition; Roasted coffee